115k views
1 vote
Can any one help me solve this question through substitution method. plz show me all the steps:

x+y/3=3
3x+y/5=1

User Atul KS
by
5.3k points

1 Answer

4 votes

By substitution method
(x,y) = ((-1)/(3) , 10) i.e. x =
(-1)/(3) and y = 10.

Explanation:

We have the following equations and using substitution method we need to find corresponding set of values of x and y:


x + (y)/(3) = 3\\ 3x+ (y)/(5) = 1 -------> eq 2

Let's find value of x in terms of y using equation 1 as:


x + (y)/(3) = 3


x= 3-(y)/(3)


x = (9-y)/(3)

Now, putting this value of x in equation 2 to find value of x:


3x + (y)/(5) = 1\\\\3((9-y)/(3) ) + (y)/(5) = 1\\\\9-y + (y)/(5) = 1\\\\(-4y)/(5) = -8\\


y = 10

Since
x = (9-y)/(3)


x = (9-10)/(3) = (-1)/(3)

Hence by substitution method
(x,y) = ((-1)/(3) , 10) .

User Dylan F
by
5.2k points